World Public Debt and Real Interest Rates - Ford, Robert (IMF Working Papers; Working Paper ;, 1995)
Real interest rates appear to have risen in virtually all industrialized countries relative to levels that prevailed in the 1960s and 1970s. There is increasing concern that this may reflect higher public debt, which is crowding out private sector activity. Over the last two decades, there has also been increasing international capital market integration. This suggests that interest rates in any country may be sensitive to global fiscal developments. This paper estimates the effects of aggregate fiscal developments in the industrialized world on real interest rates in nine industrial countries. The results imply that the increase in OECD-wide government debt since the late 1970s was a major factor explaining the rise in real interest rates.